Dysbiosis: The first hit for digestive system cancer - Mei, Si; Deng, Zhe; Chen, Yating; Ning, Dimin; Guo, Yinmei; Fan, Xingxing; Wang, Ruoyu; Meng, Yuelin; Zhou, Qing; Tian, Xuefei (Frontiers in Physiology, 2022)
Gastrointestinal cancer may be associated with dysbiosis, which is characterized by an alteration of the gut microbiota. Understanding the role of gut microbiota in the development of gastrointestinal cancer is useful for cancer prevention and gut microbiota-based therapy. However, the potential role of dysbiosis in the onset of tumorigenesis is not fully understood. While accumulating evidence has demonstrated the presence of dysbiosis in the intestinal microbiota of both healthy individuals and patients with various digestive system diseases, severe dysbiosis is often present in patients with digestive system cancer. Importantly, specific bacteria have been isolated from the fecal samples of these patients. Thus, the association between dysbiosis and the development of digestive system cancer cannot be ignored. A new model describing this relationship must be established. In this review, we postulate that dysbiosis serves as the first hit for the development of digestive system cancer. Dysbiosis-induced alterations, including inflammation, aberrant immune response, bacteria-produced genotoxins, and cellular stress response associated with genetic, epigenetic, and/or neoplastic changes, are second hits that speed carcinogenesis. This review explains the mechanisms for these four pathways and discusses gut microbiota-based therapies. The content included in this review will shed light on gut microbiota-based strategies for cancer prevention and therapy.